20. UPAYA INDONESIA DALAM PENANGANAN KASUS PEDOFILIA INTERNASIONAL DI PULAU BALI - Septia, Merita Putri; Windiani, Reni; Basith Dir, andi Akhmad (Journal of International Relations, 2016)
In this research, writer would like to analyze effort done by Indonesian government to handlepedophilia sexual harassment happened in its territory. Writer have chosen Bali as case studyas Bali is one of most favorite tourism destination both domestic and international so that itneeds special treatment from Central government and Local government. This research willbe conducted using qualitative method to describe the process and give a better understandingregarding certain issue. The research descriptive explanation depicting the background storyof pedophilia sexual harassment cases in Bali which ranked first as Indonesian provincewhich has highest cases of pedophilia, proven by the fact that more than 300 cases happenedin Bali. Writer use the Normative Theory of International relations to describe the relationbetween appropriate norms and its relations on creating laws regarding the issue. Apart fromdescriptive explanation, writer will examine on effort done by Indonesian government both interm of internal effort and external effort. According to the research result, Indonesia havedone internal effort to combat by creating Article No. 23, 2002 Indonesian Law regardingChild Protection. Indonesia also have a well-coordinated relations between Police,Immigration, and Komisi Perlindungan Anak. Externally, Indonesia also has cooperated withInterpol through National Police to have faster information exchange to reveal complicatedcases of Pedophilia.